A toroidal momentum transport equation for axisymmetric 1D transport codes. (9th March 2015) - Fable, E
Abstract: A toroidal momentum transport equation is presented, which is suited for implementation in 1D transport codes in axisymmetric geometry (e.g. tokamak plasmas). Contributions to the total toroidal momentum from the different plasma species are retained. The contributions of E × B, diamagnetic and poloidal flows are also retained. The different pieces appearing in the expression for the turbulence-driven part of the flux are obtained consistently from standard gyro-kinetic theory.